Preserve and spread of traditional plant varieties - Molla, M. (Open Schools Journal for Open Science, 2020)
The seeds of the traditional varieties which we have inherited from our ancestors thousands of years ago are vanishing in our days and with them we are losing our connection with them and the biodiversity. In this eTwinning project teachers and students aimed at becoming an ark with the mission to protect and save these seeds. We started our quest by making our questionnaire which was simple since it consisted of three questions but would ultimately tell the story of how the traditional seeds were inherited to us. Students researched within their family and neighborhood context. The findings of their research showed that only about 10% of the students found seeds of traditional vegetable varieties. Subsequently we tried to multiply these seeds by cultivating them and spreading them to our school and our community.